Fluorescence detection of pyrene-stained Bacillus subtilis LPM1 rhizobacteria from colonized patterns of tomato roots. Issue 10 (24th September 2020) - Hernández, Mónica; Ortiz-Castro, Randy; Flores-Olivas, Alberto; Moggio, Ivana; Arias, Eduardo; Valenzuela-Soto, José Humberto
Abstract : Bacillus subtilis LPM1 colonization patterns were identified by fluorescence by spreading a pyrene–water solution on the tomato roots in vivo and in vitro . Abstract : A series of water soluble 8-alcoxypyrene-1, 3, 6-trisulfonic sodium salts bearing different alcoxy lateral chains and functional end groups was synthesized and the molecular structure was corroborated by nuclear magnetic resonance spectroscopy. The photophysical properties in water analyzed by UV-Vis and static and dynamic fluorescence revealed that all of the pigments emit in the blue region at a maximal wavelength of 436 nm and with fluorescence lifetimes in the range of ns. Among them, sodium 8-((10-carboxydecyl) oxy) pyrene-1, 3, 6-trisulfonate M1 exhibits a high fluorescence quantum yield ( ϕ = 80%) and a good interaction with B. subtilis LPM1 rhizobacteria; this has been demonstrated through in vitro staining assays. Tomato plants ( Solanum lycopersicon cv. Micro-Tom) increased the release of root exudates, mainly malic and fumaric acids, after 12 h of treatment with benzothiadiazole (BTH) as a foliar elicitor. However, the chemotaxis analysis demonstrated that malic acid is the most powerful chemoattractant of the rhizobacteria Bacillus subtilis LPM1: in agar plates, a major growth (60 mm) was found for a concentration of 100 mM, while in capillary tubes, the earliest response was at 30 min with 3.3 × 10 8 CFU mL −1 . The confocal microscopic analysis carried out on the tomato roots of the pyrene stained B. subtilis LPM1 revealed that this bacterium mainly colonizes the epidermal zones, i.e. the junctions to primary roots, lateral roots and root hairs, meaning that these root hair sections are the highest colonisable sites involved in the biosynthesis of exudates. This fluorescent pyrene marker M1 represents a valuable tool to evaluate B. subtilis –plant interactions in an easy and quick test in both in vitro and in vivo tomato crops.